THE EFFECT OF USING THIEVES AND CSR STRATEGIES TO IMPROVE READING COMPREHENSION SKILL AT EIGHTH GRADE SMP KINGSTON SCHOOL, DELI SERDANG - Jingga, Jenny; Sinambela, Erika; Tampubolon, Sahlan (Jurnal Mutiara Pendidikan Indonesia, 2022)
The purpose of this study is to determine the efficacy of applying THIEVES and CSR techniques to increase reading comprehension in Kingston School grade 8 students. The researcher devised a quasi-experimental study in order to fulfil the research's goal. The participants in this study were 108 eighth-grade Kingston School students, with 36 involved in the experimental group 1 who were taught reading comprehension using the THIEVES strategy, 36 involved in the experimental group 2 who were taught reading comprehension using the CSR strategy, and the remaining 36 involved in the control group who were taught reading comprehension using the conventional strategy. A pre-test and post-test with 40 multiple-choice items were included in the data collection instrument. The results were compared and examined to determine the efficacy of the two strategies. The experimental groups 1 and 2 scored higher than the control group, according to the results of a study. THIEVES and CSR techniques are both successful in boosting reading comprehension, according to the results. The statistics also indicate that the CSR method outperforms the THIEVES technique. Keywords: reading comprehension, THIEVES Strategy, CSR Strategy